FROM DARKNESS TO LIGHT: TRANSCENDENCE IN THE SELECTED POEMS OF PHILIP LARKIN - Tneh, David C.E. (International Journal of Humanity Studies (IJHS), 2025)
This paper explores the pervasive motifs of darkness and light in the selected poetry of Philip Larkin, examining how these images underscore the central themes and emotional landscapes within his works. Larkin’s use of light and dark imagery often reflects the dichotomy between hope and despair, life and death, and the transient nature of human existence. The study aims to analyse the symbolic significance of light and dark imagery in Larkin's poetry, investigate how these motifs contribute to the thematic depth and emotional resonance of his works and enhance the understanding of Larkin’s philosophical contemplations and the philosophical tradition of naturalism that is featured strongly in his poetry. Through a close reading of his selected poems, this study employed a qualitative analysis to delve into the poet’s nuanced portrayal of light as a symbol of fleeting joy and enlightenment, juxtaposed against the encroaching darkness that symbolises existential angst and inevitable mortality. The analysis reveals that Larkin has stayed true to the philosophical tradition of naturalism, and the analysis of the selected poems reveals the contrasting images of light and dark, which effectively capture the complexities of the human condition. Light is depicted as a transient source of joy and enlightenment, while darkness represents the inevitable presence of existential dread and mortality. This juxtaposition highlights Larkin’s introspective vision and his ability to convey profound philosophical insights through his poetic artistry. There is thus a movement towards positivity and hope despite the melancholic mood of Larkin’s poetry which is often pervasive in most of his poems. By analysing these contrasting images, the paper aims to show this progression from negativity to a certain positive transcendence, thus contributing to a deeper and newer understanding of Larkin’s poetic artistry and his philosophical contemplations on life’s ephemerality.